2002
DOI: 10.1034/j.1600-0722.2002.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a convenient system for the long‐term culture and study of non‐neoplastic human salivary gland epithelial cells

Abstract: Epithelial cells appear to play an important role in the initiation and maintenance of autoimmune lesions in the salivary glands of patients with Sjogren's syndrome. Therefore, the detailed study of immunological function of salivary gland epithelial cells (SGEC) may provide useful information for the understanding of Sjögren's syndrome pathogenesis. In this report we aimed to formulate a protocol for the establishment of human non-neoplastic SGEC lines as a tool for the study of the physiology and pathophysio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 30 publications
1
78
0
Order By: Relevance
“…Primary cultures of SGEC were established from minor salivary glands as described [35]. Briefly, each lobule was cut into small fragments and set in six 75-cm 2 flasks with basal epithelial medium (a 3:1 mixture of Ham's F-12 and DMEM) supplemented with 2.5% FBS, EGF (10 ng/mL), hydrocortisone (0.4 mg/mL), insulin (0.5 mg/ mL), penicillin (100 IU/mL) and streptomycin (100 mg/mL) and incubated at 371C with 5% CO 2 .…”
Section: Cultures Of Sgec and Treatmentmentioning
confidence: 99%
“…Primary cultures of SGEC were established from minor salivary glands as described [35]. Briefly, each lobule was cut into small fragments and set in six 75-cm 2 flasks with basal epithelial medium (a 3:1 mixture of Ham's F-12 and DMEM) supplemented with 2.5% FBS, EGF (10 ng/mL), hydrocortisone (0.4 mg/mL), insulin (0.5 mg/ mL), penicillin (100 IU/mL) and streptomycin (100 mg/mL) and incubated at 371C with 5% CO 2 .…”
Section: Cultures Of Sgec and Treatmentmentioning
confidence: 99%
“…Few studies have reported the isolation and growth of primary epithelial cells from explants of salivary gland tissues (Sens et al 1985;Sabatini et al 1991;Okura et al 1993;Dimitriou et al 2002). However, maintenance of the acinar phenotype for long periods of time and preservation of the acinar cell functionality have not been demonstrated yet (Redman and Quissell 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The purity and epithelial origin of cultured SGEC lines was routinely verified by morphology, the uniform expression of epithelial-specific markers and the absence of markers indicative of lymphoid/monocytoid cells (16). Distinct SGEC lines have not been found to differ in morphological features, proliferation rate or survival (16).…”
Section: Cell Linesmentioning
confidence: 99%
“…Non-neoplastic, long-term cultured SGEC lines and salivary gland fibroblasts were established from minor salivary gland biopsy samples obtained with informed consent from patients undergoing diagnostic evaluation for possible Sjögren's syndrome, as previously described (16). The purity and epithelial origin of cultured SGEC lines was routinely verified by morphology, the uniform expression of epithelial-specific markers and the absence of markers indicative of lymphoid/monocytoid cells (16).…”
Section: Cell Linesmentioning
confidence: 99%